Is Democracy Effective against Coronavirus? An Analysis of Citizens' Opinions in Italy - Marco Maraffi; Simona Guglielmi; Ferruccio Biolcati; Antonio M. Chiesi; Giulia M. Dotti Sani; Riccardo Ladini; Francesco Molteni; Paolo Segatti; Cristiano Vezzoni; Andrea Pedrazzani (Partecipazione e Conflitto, 2021)
The social and political implications of the COVID-19 pandemic are receiving increasing attention in the literature. This article aims to contribute to this fast-growing research programme by focusing on the degree to which Italian citizens perceive democratic institutions as effective in coping with crises like the COVID-19 emergency. We put forward a set of hypotheses whereby negative evaluations of the effectiveness of democracy can be associated with social proximity to the disease and with perceived health and economic threats. We also argued that political factors can interact with such threats. Moreover, we hypothesised that certain factors dealing with the concepts of social capital and civic culture can help inhibit negative opinions about the effectiveness of democracy. To test these hypotheses, we analysed public opinion data collected in Italy between April and July 2020 using a Rolling Cross-Section survey design. The data showed that evaluations of democracy became more negative with social proximity to the disease and with individual perceived vulnerability, understood in health and economic terms. Our findings also highlighted that certain social factors which "underpin" democracy moderated negative evaluations. Finally, political factors like ideology and government appraisal shaped the relationship between individual threats and evaluations of democracy.